2008
DOI: 10.1111/j.1365-2133.2007.08405.x
|View full text |Cite
|
Sign up to set email alerts
|

Segregation analysis in X-linked ichthyosis: paternal transmission of the affected X-chromosome

Abstract: These data strongly suggest that STS gene deletion occurred in the male meiosis probably due to an intrachromosomal event, recombination between S232 sequences on the same DNA molecule, or during the process of DNA replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
1
4
1
Order By: Relevance
“…[32] A more recent study on seven unrelated sporadic cases of XLI demonstrated, by means of short tandem repeats, the paternal transmission to the mother of the proband in 5 out 7 cases (two cases were uninformative), suggesting that the STS deletion occurred in the male meiosis. [33] In contrast, in our case, the mother of the patient was negative to MLPA analysis indicating that the genomic rearrangement arose in the maternal meiosis. Thus, STS deletion seems to occur much more frequently in male gonads, in keeping with the high number of cell divisions in spermatogenesis.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…[32] A more recent study on seven unrelated sporadic cases of XLI demonstrated, by means of short tandem repeats, the paternal transmission to the mother of the proband in 5 out 7 cases (two cases were uninformative), suggesting that the STS deletion occurred in the male meiosis. [33] In contrast, in our case, the mother of the patient was negative to MLPA analysis indicating that the genomic rearrangement arose in the maternal meiosis. Thus, STS deletion seems to occur much more frequently in male gonads, in keeping with the high number of cell divisions in spermatogenesis.…”
Section: Discussioncontrasting
confidence: 79%
“…A first segregation study reported the paternal origin of the X chromosome transmitted to a daughter with a de novo deletion of STS . A more recent study on seven unrelated sporadic cases of XLI demonstrated, by means of short tandem repeats, the paternal transmission to the mother of the proband in 5 out 7 cases (two cases were uninformative), suggesting that the STS deletion occurred in the male meiosis . In contrast, in our case, the mother of the patient was negative to MLPA analysis indicating that the genomic rearrangement arose in the maternal meiosis.…”
Section: Discussionsupporting
confidence: 64%
“…This approach is supported by a review of cases and series of XLI published in the literature to ascertain all sporadic cases where carrier testing was done in the mother of the affected boy. A total of 21 mothers of sporadic cases with proven STS deletion had been tested and in 19 cases the mother was found to be a carrier of the deletion (Ahmed et al,1998;Valdes-Flores et al, 2001;Toral-Lopez et al, 2008;Hosomi et al, 2008). Furthermore, Toral-Lopez et al reported on molecular analysis of families to identify the parental origin of the affected X-chromosome in seven unrelated sporadic cases of XLI (Toral-Lopez et al, 2008).…”
Section: Molecular Analysismentioning
confidence: 99%
“…Several theories have been proposed to explain this phenomenon to date 10 . A recent study has suggested that STS deletion occurs in the male meiosis 11 …”
Section: Introductionmentioning
confidence: 99%
“…10 A recent study has suggested that STS deletion occurs in the male meiosis. 11 The STS gene consists of 10 exons that extend for 146 kb. Up to 90% of the described mutations of this gene are complete deletions.…”
Section: Introductionmentioning
confidence: 99%